Two sweaters for my father writing about knitting - Klass, Perri 1958- (Sioux Falls, S.D XRX Books, 2004)
Essays about knitting and its place and impact in the lives of those who knit
Essays previously published in popular magazines, 1992-2004
13
Keywords: Knitting -- Social aspects; Knitting